FEATURES OF THE USE OF ARTIFICIAL NEURAL NETWORKS IN DIGITAL MARKETING - VENHER, Evheniy; NIKULCHA, Valentyn (Herald of Khmelnytskyi National University. Economic sciences, 2023)
This article examines the possibilities and advantages of using artificial neural networks in digital marketing, describes different types of neural networks. It was determined that neural networks are complex structures created from artificial neurons that can accept multiple inputs to obtain a single output. Artificial neural networks are a subsystem of machine learning, which in turn is a subsystem of artificial intelligence. In the processes of creating content for "sales funnels" and optimizing it to generate quality traffic, neural networks have long proven themselves as a worthy replacement for traditional approaches. Considerable attention in this study is focused on studying the possibilities of using neural networks for data analysis, forecasting trends and solving marketing analytics problems. The main types of artificial neural networks that are currently used in marketing activities are systematized and classified. Key functions that can be performed by neural networks in the context of digital marketing are highlighted, such as forecasting the demand for goods and services, researching consumer behavior, analyzing the competitive situation on the market, recommendations for managing product portfolios, automating business processes, etc. It is emphasized that marketers and managers can use neural networks to improve three strategic areas: segmentation, targeting and positioning.It is noted that attempts to systematize knowledge about artificial intelligence and machine learning in marketing provided the formation of theoretical foundations for the development of consumer-oriented applications in the context of consumer experience and personalized communications. Despite the significant number of advantages of using artificial neural networks in digital marketing, there are also a number of disadvantages and threats associated with artificial intelligence technologies. The use of neural networks is an effective and promising tool in digital marketing, but it requires significant technical and financial costs, and also raises ethical issues that must be resolved before using neural networks for marketing purposes. Further research in this direction can help companies achieve more effective results in their digital marketing strategy.